Performance enhancement of modified solar distillers using synthetic nanocomposites, reflectors, cover cooling, and ultrasonic foggers: Experimental approach. (April 2023) - Kandeal, A.W.; El-Shafai, Nagi M.; Hammad, Farid A.; Elsharkawy, Marwan; El-Mehasseb, Ibrahim; Amro, M.I.; El-Samadony, M.O.A.; Sharshir, Swellam W.
Highlights: Augmented performance of solar still was evaluated via integrating evaporation and condensation enhancers. Synthetic nanocomposites were developed, characterized, and used with different concentrations. Thermo-economic performance was investigated compared to conventional solar still. Productivity, energy efficiency, and average exergy efficiency augmentations reached 113.72, 96, and 167.62 %, respectively. Abstract: This work aimed to develop the thermo-economic performance of solar still (SS) via various additives. On the one hand, to improve the thermophysical properties of the basin saline water, two nanocomposites were utilized in the modified SSs (MSSs). In MSS1, chitosan @ graphene oxide (Cs@GO) was used, whereas chitosan @ nickel oxide (Cs@NiO), was provided in MSS2. The concentration influence on the yield was investigated considering three ratios (0.1, 0.2, and 0.3 wt%). The selected concentration (0.3 wt%) was used for the upcoming cases being better than others. At this weight ratio, the yield was augmented by 72.7, and 57.5 % for MSS1, and MSS2, respectively, compared to CSS. In the first case (Case I), a glass lid cooling unit was attached to the MSSs to boost the condensation rate. In the second case (Case II), top and bottom external reflectors were fixed on the MSSs. Then, Case III contained both cover cooling and reflectors. In addition to these enhancers, ultrasonic atomizers were placed on the basin of MSSs in Case IV. In each experiment, both MSS1 and MSS2 were simultaneously compared to conventional SS (CSS). All cases showed good thermo-economic performances. The best performance was obtained, especially in terms of yield, from MSS1 in Case IV, at which the production, energy, and exergy efficiencies were improved by 113.72, 96, and 167.62 %, respectively.